Accuracy of energy yield prediction of photovoltaic modules - Jyotirmoy Roy; Tom Betts; Ralph Gottschalg (2012)
The uncertainty analysis of irradiance and temperature measurements in relation to the energy yield prediction of the photovoltaic (PV) modules are presented. A Monte Carlo simulation approach is demonstrated separately to propagate the monthly and annual measurement uncertainties of irradiance and temperature to annual energy yield prediction uncertainty for two commercially available PV modules. The annual irradiation uncertainty as measured with a thermopile pyranometer is calculated as ±1.56%. Uncertainty of the annual average of ambient temperature measurement is calculated as ±0.08 °C. Finally, the uncertainty in the energy yield estimation of the PV devices is determined as 2.8 and 15.5% for crystalline silicon (c-Si) and copper indium gallium (di)selenide (CIGS) modules, respectively.